2022
DOI: 10.3389/fnagi.2022.830858
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils, Stroke-Associated Pneumonia, and Outcome After Mechanical Thrombectomy for Acute Ischemic Stroke

Abstract: BackgroundEosinophils contribute to antibacterial defense by releasing mitochondrial DNA, which are decreased in patients with acute ischemic stroke (AIS). However, the impact of eosinophils on stroke-associated pneumonia (SAP) among patients with AIS remains unclear. Moreover, whether SAP is in the path of the association between eosinophils and clinical outcomes also remains unclear. We aimed to assess the relationships between eosinophils, SAP, and clinical outcome after mechanical thrombectomy in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…[12,17] According to previous research, stroke induced a transient reduction in the number of circulating eosinophils; lower eosinophil counts were correlated with stroke severity and the poor prognosis of AIS patients. [12,14,29] Our study also confirmed that the LVO group had reduced eosinophil counts, but eosinophils didn't correlate with the presence of LVO.…”
Section: Discussionsupporting
confidence: 70%
“…[12,17] According to previous research, stroke induced a transient reduction in the number of circulating eosinophils; lower eosinophil counts were correlated with stroke severity and the poor prognosis of AIS patients. [12,14,29] Our study also confirmed that the LVO group had reduced eosinophil counts, but eosinophils didn't correlate with the presence of LVO.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, certain characteristics that were not examined in our analysis may still have a role in the potential overall causal pathway for reperfusion and functional outcome. First pass effect, 26 blood-brain barrier permeability, 27 and inflammatory markers 28,29 have been examined and found to be responsible for a small proportion of the overall thrombectomy treatment effect. Factors such as preexisting cerebrovascular disease or occult neurodegeneration, the severity and type of premorbid functional deficits, and the presence and severity of hemorrhagic transformation after thrombectomy may also affect EVT outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils were consistently negatively correlated with PT in patients with anti-NMDAR encephalitis. Eosinophils can induce the activation of M2 microglia by secreting IL-4 and IL-13 to promote the elimination of inflammation and play the neuroprotective role of microglia ( 25 ). This may explain why patients in the severe group had lower eosinophil levels.…”
Section: Discussionmentioning
confidence: 99%